Distruzione intenzionale del patrimonio culturale nel diritto internazionale - Cunsolo, Francesco Paolo (The University of Edinburgh, 2025)
The protection of cultural heritage is one of the great challenges of the contemporary world, due to the immense implications that culture, in all its tangible and intangible manifestations, has on the political, economic and social level. Over the years, the transmission of cultural heritage has progressively become a central theme of international debate, generating an increasingly widespread interest on the part of the international community in the protection of culture, in all its forms. Among the many threats currently affecting the protection of cultural heritage (war, climate change, urban development, mass tourism) and calling for a vigorous response from the international community, the deliberate suppression and destruction of cultural heritage is probably the most serious and pressing. Starting from this point, two questions arise spontaneously: what does “intentional destruction of cultural heritage” exactly mean? And what instruments does international law have at its disposal to counter this phenomenon? Over the years since its establishment, UNESCO has promoted the adoption of numerous international conventions to prevent cultural destruction in times of war, illicit trafficking of cultural properties, the protection of world cultural heritage and underwater cultural heritage, the preservation of living cultures and the protection of the diversity of cultural expressions. However, despite this rich and varied normative system, the obligations undertaken by States in this field are still predominantly treaty-based, i.e. founded on their consent expressed in acts of ratification or accession to the relevant treaties. On the contrary, the assessment of customary international rules regarding the protection of cultural heritage from the most serious forms of destruction is still uncertain and requires careful inquiry. According to the Draft Conclusions submitted in 2018 by the International Law Commission, in order to determine the existence and content of a rule of customary international law, it is necessary to ascertain whether there is a general practice (diuturnitas or usus), primarily referred to the States’ behavior, and if this practice is accepted as law (opinio iuris sive necessitatis). In the case of cultural heritage protection from acts of deliberate destruction, various manifestations of practice must be taken into account, starting with international jurisprudence, with special regard to international criminal proceedings (mostly from the International Criminal Tribunal for the former Yugoslavia and the International Criminal Court), and also International Court of Justice case law. Moreover, the statements of international organizations and States before the acts of destruction of cultural property (e.g. the unanimous condemnation reaction of the international community to the destruction of the Bamiyan Buddhas in 2001), as well as Security Council resolutions, soft law instruments and national jurisprudence, constitute important elements of practice that must be considered. The aim of this work is to frame and critically assess all the instruments available in public international law to deal with the phenomenon of intentional destruction of cultural heritage, in order to ascertain the presence, or possible state of formation, of a customary norm prohibiting such destructive actions, whether in armed conflict or in peacetime.
La distruzione intenzionale del patrimonio culturale nel diritto internazionale
The intentional destruction of cultural heritage in international law
Keywords: cultural heritage destruction; human rights; international law; war crime; crime against humanity